2023
DOI: 10.3847/1538-4357/ad022b
|View full text |Cite
|
Sign up to set email alerts
|

JWST: Deuterated PAHs, PAH Nitriles, and PAH Overtone and Combination Bands. I. Program Description and First Look

C. Boersma,
L. J. Allamandola,
V. J. Esposito
et al.

Abstract: A first look is taken at the NIRSpec 1–5 μm observations from James Webb Space Telescope program 1591 that targets seven objects along the low-mass stellar life cycle with polycyclic aromatic hydrocarbon (PAH) emission. Spectra extracted from a 1.″5 radius circular aperture are explored, showing a wealth of features, including the 3 μm PAH complex, the PAH continuum, and atomic and molecular emission lines from H i, He, H2, and other species. CO2- and H2O-ice absorption and CO emission is also seen. Focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…Observations from the James Webb Space Telescope (JWST) are now facilitating higher-resolution measurements in the 1–5 μm region. 52 There is evidence of emission features in the 4.51–4.52 μm region in observation toward young planetary nebulae BD+303639 and NGC7027. 52 In previous studies, some strong emission lines in this region were observed from M17 and from Orion Bar.…”
Section: Astrochemical Implicationsmentioning
confidence: 95%
See 4 more Smart Citations
“…Observations from the James Webb Space Telescope (JWST) are now facilitating higher-resolution measurements in the 1–5 μm region. 52 There is evidence of emission features in the 4.51–4.52 μm region in observation toward young planetary nebulae BD+303639 and NGC7027. 52 In previous studies, some strong emission lines in this region were observed from M17 and from Orion Bar.…”
Section: Astrochemical Implicationsmentioning
confidence: 95%
“…52 There is evidence of emission features in the 4.51–4.52 μm region in observation toward young planetary nebulae BD+303639 and NGC7027. 52 In previous studies, some strong emission lines in this region were observed from M17 and from Orion Bar. 34,53 It should be noted that our measurement concern the absorption of cold 1-CNN + –He, and therefore differences between the band profiles of this complex and emission of UV pumped 1-CNN + are expected.…”
Section: Astrochemical Implicationsmentioning
confidence: 95%
See 3 more Smart Citations